THE DISTRIBUTION OF BATIK INDUSTRY TOWARD SOCIETY INCOME IN KENEP VILLAGE SUKOHARJO SUB DISTRICT SUKOHARJO DISTRICT 2018 - Dewi, Try Solekah; Sudargono, Agus; Rohsulina, Pranichayudha (Journal of Geography Science and Education, 2019)
This study aims to know : 1) the influence of Batik industry on society income in Kenep Village, 2) the distribution of Batik Industry in Kenep Village. This study used qualitative descriptive method and sampling population for the sampling method. The data collection method in this research is through field observation, interview, and questionairre documentation while the data analyse method used frequency table, cross table analysis, map analysis, and qualitative descriptive analysis. This study found that the majority of Batik Industry owners was dominated by woman in the age range 15-64 years old and mostly they have already married. Besides, mostly of them were graduated from Junior High School. Batik Kedunggudel is an inheritance industry that produces written, stamp, and printing Batik. The market range of Batik Kedunggudel in Kenep Village includes Java, Sulawesi, and Kalimantan Island. The marketing method of Batik Kedunggudel is : using online application and shipping service. The majority of labors of this industry is dominated by man. This industry has capital business around <Rp.51.000.000 with average income around <Rp.10.000.000 each month, while the labor obtain Rp.1.500.000 as their salary per month, not including wholesale salary.